Relationship between reading and writing performance / Rosita Aminullah …[et al.] - Aminullah, Rosita; Joseph, Caroline; Bakar, Sulaila; Mat Pardi, Khalid (2013)
This pilot study is aimed at investigating the relationship between reading and writing performance among university ESL students. The subjects of the study were students of English language from various faculties of UiTM Pahang. The data used was taken from the students' results in two reading comprehension tests and one writing test in their English for Academic Purposes (BEL311) final examination paper. The data collected was analyzed through SPSS 20 to provide indicators of their performance that can potentially reflect the reading and writing connection. The findings of the study showed that there some degree of correlation between the students' reading and writing performance. The research shows some connection between the constructs of reading and writing. The findings point to the need of nurturing greater success in the students' reading and writing abilities. The connections between the two language proficiency skills can be exploited for the benefits of university ESL students in general and UiTM Pahang ESL students